Net Neutrality, Prioritization and the Impact of Content Delivery Networks - Pio Baake; Slobodan Sudaric (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2018)
We analyze competition between Internet Service Providers (ISPs) where consumers demand heterogeneous content within two Quality-of-Service (QoS) regimes, Net Neutrality and Paid Prioritization, and show that paid prioritization increases the static efficiency compared to a neutral network. We also consider paid prioritization intermediated by Content Delivery Networks (CDNs). While the use of CDNs is welfare neutral, it results in higher consumer prices for internet access. Regarding incentives to invest in network capacity we show that discriminatory regimes lead to higher incentives than the neutral regime as long as capacity is scarce, while investment is highest in the presence of CDNs.
Keywords: L13; L51; L96; 330; content delivery network; investment; net neutrality; prioritization